Tradisi Rokat Polo Perspektif Konseling Islam di Kabupaten Sumenep - Gusdur, Gusdur; Abd. Mughni , Abd. Mughni (Fakultas Dakwah Universitas Ibrahimy, 2022)
Indonesia has many islands that stretch from Sabang to Merauke, this is what brings In- donesia to a rich variety of languages and traditions, and it is inevitable that each tradition of each region undergoes significant changes according to the times and not only changes that occur, assumptions and statements of pros and cons can also occur in the internal tradi- tion. The purpose of the study was to describe the values of Islamic counseling contained in the Rokat Polo tradition in Sumenep Regency. The research method used is a qualitative re- search method. Qualitative research method as a research procedure that produces descripti- ve data in the form of written or spoken words from people or observable behavior, with an ethnographic research model. From the results of research on the Rokat Polo tradition, the- re are Islamic counseling values, including: (1) Dhikr, (2) Building Islamic Brotherhood, (3) Solidarity, (4) Caring for the natural surroundings and (5) Patience.